In vitro and in vivo evaluation of a novel testosterone transdermal delivery system (TTDS) using palm oil base - Haron, D.E.M.; Chik, Z.; Noordin, M.I.; Mohamed, Z. (2015)
Objective (s): Transdermal preparations for testosterone are becoming popular because of their unique advantages such as avoidance of first-pass effect, convenience, improved bioavailability, and reduction of systemic side effects. A novel testosterone transdermal delivery system (TDDS) was developed using a palm oil base called HAMIN (TM) (a commercial product) and tested using in vitro and in vivo skin permeability test methods. Materials and Methods: The physical characteristics of the formulation such as particle size and viscosity were determined by using Franz diffusion cell and Brookfield viscometer, respectively. In vivo skin permeability test was performed on healthy rabbits through the skin. Testosterone in serum was analyzed using the validated Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) technique. Results: In vitro study showed that the cumulative amount of testosterone diffused was between 40 to 1400 ngcm(-2) over a period of five hr after application of TDDS through the artificial Strat-M (TM) membrane. In the in vivo rabbit skin permeability test, the results indicated that testosterone was well absorbed with a mean C-max and T-max of 60.94 ngml(-1) and 2.29 hr after application of TDDS while no increase was observed in placebo treatment. Particle size analysis ranged from 79.4 nm to 630.0 nm for placebo and 97 to 774.0 nm for TDDS. Conclusion: The formulation was successfully prepared using HAMINTM, which has demonstrated great potential for topical delivery of testosterone.